Karol Reyzner (1803-1887) – wydawca, księgarz i drukarz poznański - Jazdon, Artur (Biblioteka Uniwersytecka, 2009)
The book market in Poznań at the turn of the 1920s and the 1930s got a particular boost and encouragement. Following a temporary softening of the strict policy of the German authorities towards the Poles, Polish lending libraries and bookshops publishing in Polish and for the Poles began to crop up. The press market, publishing both local newspapers and journals, enjoyed a particular development. Karol Reyzner was a lesser known publisher and undoubtedly stayed in the shade of more eminent and prominent figures such as Walenty Stefański, Jan K. Żupański, Napoleon Kamieński, Antoni Popliński and Ludwik Merzbach. His influence upon the local book market was far less intensive than that of the above mentioned publishers as his publications were not that numerous or important. However, K. Reyzner managed to survive on the market for as long as half a century, i.e. for a much longer period than many other prominent local Polish publishers of the time. Publishing primarily books for less educated people and specializing in publications with no scientific or literary aspirations, simple and cheap judging from the editorial standards, he nevertheless carried out an important social function. The present article discusses the history of Reyzner’s printing office and its publishing output, additionally outlining the role of the lending library attached to the printing office – the first one managed by a Pole and targeted at the local Polish population. The analysis of the still existing catalogues of the library indicates that, unlike the publishing activity of the firm, the lending library addressed much more cultured and refined reader, which is manifested by the content of the collection that included many accomplished works written by prominent authors or researchers of the time.
Karol Reyzner (1803-1887) – Poznań-based publisher and printer
Keywords: Wielkopolska (Greater Poland) – 19th c.; printing industry; publishing movement; history – 19th c.; lending libraries; readership; book lending – 19th c